Influence of carbon support properties on the electrocatalytic activity of PtRuCu nanoparticles for methanol and ethanol oxidation. (28th September 2017) - Comignani, Vanina; Sieben, Juan Manuel; Sanchez, Miguel D.; Duarte, Marta M.E.
Abstract: This work set out to explore the influence of kind and surface condition of carbon supports on the electrocatalytic activity of trimetallic PtRuCu alloy nanoparticles. The structure, composition, particle size and catalyst loading were determined by XRD, EDX, XPS, TEM and ICP-AES analysis. XRD studies revealed that support physical characteristics and surface conditions have an important influence in lattice strain, while XPS pointed out that a strong electronic interaction exists between the particles and the carbon support. Electrochemical experiments showed that the activated carbon black supported PtRuCu catalyst exhibits the best performance for methanol and ethanol oxidation and the lowest poisoning rate. The superior catalytic activity of this electrode can be rationalized in terms of metal-support interaction, Pt utilization efficiency and electrical conductivity of the carbon support. Furthermore, the as-prepared electrode exhibits 13 and 7 times higher activity towards methanol and ethanol oxidation when compared with a PtRu/C commercial catalyst. Highlights: PtRuCu particles of 3 nm were deposited on treated and pristine carbon black and MWCNTs. The nature and state of the support have an important influence in lattice strain. A strong electronic interaction between the particles and the support was detected. PtRuCu/CGA showed 13 and 7 times higher activity for MOR and EOR than PtRu/C. Poisoning rate was almost 2 times lower than that on PtRu/C.